Experimental study into optimal interdependence of energy-time costs for emptying a dry dock - Khristo, Pavel (Eastern-European Journal of Enterprise Technologies, 2018)
The influence of discrete properties of the microprocessor control systems based on Arduino Due on the accuracy of the physical model of the dock pumping station by modeling in MATLAB was assessed. In this case, such factors were taken into account as the PWC switching period, the quantization pitch by level and by time of ADC and DAC of the microprocessor, the time of the program cycle execution, noise of the least significant discharges of ADC, noise and inertia of the current sensor, as well as deviation of parameters of capacitive filters, included in the feedback channels by voltage, from the nominal values, load the converter and voltage drop at the terminals of the battery. The results of calculations revealed that this influence can be neglected and the data, collected using a physical model of the dock pumping station, are reliable. Through physical simulation, the experimental correlation between energy-time costs of emptying the chamber of a dry dock was obtained, which proves the possibility of significant energy saving when the process is optimized by the appropriate criterion. It became possible thanks to multiple numerical solution of the edge problem directly on a physical model. The obtained characteristic suggests that at a short time of the process of chamber emptying, energy saving, which is achieved through optimal control of an electric drive of the pump, is relatively small compared with the option of an unregulated electric drive. However, at dragging out the process, it can reach the values at the level of 13 %. It is also noteworthy that beginning from some value of time of dry dock chamber emptying, the energy practically does not change, which makes it rational to introduce an idle pause in the law of optimal control of the object. Thus, the possibility and feasibility of optimizing the process of dry (bulk – liquid) dock chamber emptying by the energy consumption criterion was proved experimentally.